The Evolutionary Advantage in Mammals of the Complementary Monoallelic Expression Mechanism of Genomic Imprinting and Its Emergence From a Defense Against the Insertion Into the Host Genome - Kaneko-Ishino, Tomoko; Ishino, Fumitoshi (Frontiers in Genetics, 2022)
In viviparous mammals, genomic imprinting regulates parent-of-origin-specific monoallelic expression of paternally and maternally expressed imprinted genes (PEGs and MEGs) in a region-specific manner. It plays an essential role in mammalian development: aberrant imprinting regulation causes a variety of developmental defects, including fetal, neonatal and postnatal lethality as well as growth abnormalities. Mechanistically, PEGs and MEGs are reciprocally regulated by DNA methylation of germ-line differentially methylated regions (gDMRs), thereby exhibiting eliciting complementary expression from parental genomes. The fact that most gDMR sequences are derived from insertion events provides strong support for the claim that genomic imprinting emerged as a host defense mechanism against the insertion in the genome. Recent studies on the molecular mechanisms concerning how the DNA methylation marks on the gDMRs are established in gametes and maintained in the pre- and postimplantation periods have further revealed the close relationship between genomic imprinting and invading DNA, such as retroviruses and LTR retrotransposons. In the presence of gDMRs, the monoallelic expression of PEGs and MEGs confers an apparent advantage by the functional compensation that takes place between the two parental genomes. Thus, it is likely that genomic imprinting is a consequence of an evolutionary trade-off for improved survival. In addition, novel genes were introduced into the mammalian genome via this same surprising and complex process as imprinted genes, such as the genes acquired from retroviruses as well as those that were duplicated by retropositioning. Importantly, these genes play essential/important roles in the current eutherian developmental system, such as that in the placenta and/or brain. Thus, genomic imprinting has played a critically important role in the evolutionary emergence of mammals, not only by providing a means to escape from the adverse effects of invading DNA with sequences corresponding to the gDMRs, but also by the acquisition of novel functions in development, growth and behavior via the mechanism of complementary monoallelic expression.